2020
DOI: 10.3389/fchem.2020.550862
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Insertion of Molecular Hydrogen in Tetrahydrofuran Hydrate With the Help of Acidic Additives

Abstract: Among hydrogen storage materials, hydrogen hydrates have received a particular attention over the last decades. The pure hydrogen hydrate is generated only at extremely high-pressure (few thousands of bars) and the formation conditions are known to be softened by co-including guest molecules such as tetrahydrofuran (THF). Since this discovery, there have been considerable efforts to optimize the storage capacities in hydrates through the variability of the formation condition, of the cage occupancy, of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Such an observation is confirmed by recent experimental results obtained on the H 2 long-range diffusion in gas hydrate-containing H-bond defects. In such ionic hydrates, the H 2 O relaxation occurs on a shorter timescale than hydrates without H-bond defects [46,47], facilitating cage deformation [48]; thus, the H 2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49]. H2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an observation is confirmed by recent experimental results obtained on the H 2 long-range diffusion in gas hydrate-containing H-bond defects. In such ionic hydrates, the H 2 O relaxation occurs on a shorter timescale than hydrates without H-bond defects [46,47], facilitating cage deformation [48]; thus, the H 2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49]. H2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49].…”
Section: Resultsmentioning
confidence: 99%
“…In such ionic hydrates, the H 2 O relaxation occurs on a shorter timescale than hydrates without H-bond defects [46,47], facilitating cage deformation [48]; thus, the H 2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49]. H2 diffusion is measured to be faster than in the same hydrate without H-bond defects [49]. The most probable origin of a lower activation energy for the higher-occupancy systems is the deformation of the cage due to the increased cage occupancy.…”
Section: Resultsmentioning
confidence: 99%
“…Clathrates containing polar guests offer an effective gas-storing material since they form at low pressures. In particular, polar guests such as tetrahydrofuran (THF) and dioxolane form clathrates already at atmospheric pressures. Recently, a better hydrogen storage was attained by the inclusion of perchloric acid as an additive to THF clathrate . In principle, polar molecules might induce additional defects in the host lattice that facilitate the uptake and diffusion of fuel gas molecules in the clathrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the issues related to formation of the hydrate, the hydrogen-insertion mechanism plays also a crucial role not only at a fundamental level, but also in view of potential applications. In a study reported by Nguyen et al, the enhancement of the H 2 insertion within the THF hydrate achieved with the co-inclusion of acidic additive [11]. In gas hydrate structure, the acidic additive acts as a "flexibilizer" of the water cage through the addition of chemical water H-bond defects -promoting H 2 inter-cage diffusion [12].…”
Section: Introductionmentioning
confidence: 99%